Current research on the use of HCI in decision-making to build digital musical instruments: A survey - Vieira, Rômulo; Rocha, Gabriel; Schiavoni, Flávio Luiz (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2020: Anais do XIX Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2020)
Over the past four decades, there has been an increase in the spread of digital musical instruments (DMIs), largely due to the ease of access to cheap technologies with great processing and storage power. As such systems are flexible and can be easily reconfigured, there are few restrictions on their creation. In this context, this paper is based on techniques from the field of human-computer interaction (HCI) to propose a list of decisions to be taken into account when creating a DMI, observing its gains and losses, in order to find a common point for the building of this equipment.